Teachers’ Commitment and Public Service: An Exploration of Professional Dedication in Education - Rasul M Abdurasid (International Journal of Sustainable and Integrated Studies, 2026)
The study explored teachers’ public service and professional commitment, the factors influencing their professional dedication, and the role of school leadership and educational supervision in strengthening commitment. The study was anchored in Self-Determination Theory, Organizational Commitment Theory, and Public Service Motivation Theory. It was conducted at Tubig Tanah Pilot Elementary School in Bongao, Tawi-Tawi, with seven (7) Classroom Advisers from Kinder to Grade six (6) selected through purposive sampling. Data were gathered through semi-structured one-on-one interviews and a focus group discussion and were examined using thematic analysis. The findings revealed that teachers perceived public service and professional commitment as learner-centered, community-oriented, inclusive, supportive, future-oriented, caring, and dedicated. Teachers viewed their roles as extending beyond classroom instruction to mentoring learners, promoting holistic development, modelling values, encouraging community participation, and preparing responsible citizens. However, their commitment was affected by limited resources, diverse learner needs and behaviors, insufficient parental support, difficult collegial relationships, emotional and mental demands, and curriculum and systemic challenges. Collaborative school culture, supportive leadership, trust and recognition, resource support, professional guidance, encouragement, professionalism, and integrity emerged as important conditions for sustaining teachers’ commitment. The study concludes that teacher commitment is shaped by both personal dedication and the organizational and interpersonal conditions within the school. It recommends strengthening supportive leadership, professional growth opportunities, teacher well-being, autonomy, collaboration, resource support, and positive relationships among school stakeholders. The study aligns primarily with SDG 4 – Quality Education, SDG 8 – Decent Work and Economic Growth, and SDG 16 – Peace, Justice, and Strong Institutions. Its sustainability impact relates to strengthening educational, institutional, community, and governance sustainability through sustained teacher commitment, supportive school environments, and improved public educational service.